Low Operating Voltage and Immediate Read‐After‐Write of HZO‐Based Si Ferroelectric Field‐Effect Transistors with High Endurance and Retention Characteristics - Bong Ho Kim; Song‐Hyeon Kuk; Seong Kwang Kim; Joon Pyo Kim; Yoon‐Je Suh; Jaeyong Jeong; Chan Jik Lee; Dae‐Myeong Geum; Young Joon Yoon; Sang Hyeon Kim (Advanced Electronic Materials, 2024)
Abstract The study demonstrates HfZrOx (HZO)‐based Si ferroelectric field‐effect transistors (FeFETs) with a low operating voltage (1.5 V) and immediate read‐after‐write operation (100 ns) via HZO thickness scaling, electron‐beam‐irradiation (EBI) treatment, and interfacial layer (IL) scavenging. With these three strategies, reduced operating voltage, immediate read‐after‐write capability, and improved endurance (>108 cycles) and retention (extrapolated 10‐year) characteristics are achieved in FeFETs. The improved characteristics of FeFETs are attributed to the reduced operating voltage by HZO thickness scaling, the ferroelectric orthorhombic phase‐oriented crystallization by EBI treatment, and the reduced gate voltage drop across the IL and reduced depolarization field by the IL scavenging. It is believed that this work contributes to the development of low‐power and fast‐read FeFETs.